Technological Development and Economic Growth in Turkiye - KOÇAK, MURAT (İstanbul Kültür Üniversitesi, 2025)
This thesis examines the relationship between technological development and economic growth through the case of Türkiye. With the transition to a knowledge-based economy, technology has become a determining factor on countries' production structures, productivity levels, and competitiveness. In the study, the definition of technology and the process of technological change are addressed; within the framework of classical, neoclassical, Schumpeterian, evolutionary, and development economics approaches, the effects of technology on economic growth are evaluated. In the theoretical part of the thesis, the concepts of technology policies, technology transfer, and the national innovation system are examined; successful technoeconomic policy practices are analyzed through the examples of the United States of America, Japan, and South Korea. Within this scope, science and technology policies implemented in Türkiye in the pre-1980 and post-1980 periods are discussed from a historical perspective. In the empirical analysis section, by using data for Türkiye, the relationships between Gross Domestic Product and research and development expenditures, high-technology exports, patent applications, education expenditures, foreign direct investment, and inflation are examined using econometric methods. The findings obtained reveal that technological indicators positively affect economic growth.
Keywords: Technological Development; Economic Growth; Technology Policies